Pelatihan Pengolahan Limbah Ampas Kelapa menjadi Tepung Kelapa sebagai Alternatif Pengganti Tepung Terigu dalam Pembuatan Kue di Desa Utaurano Kabupaten Kepulauan Sangihe: Training on Processing Coconut Waste into Coconut Flour as an Alternative to Substitute Wheat Flour in Making Cookies in Utaurano Village, Sangihe Islands Regency - Banne, Yos; Dumanauw, Jovie Mien; Maramis, Rilyn Novita; Rindengan, Elvie Rifke; Ulaen, Selfie Petronela Joice; Nahor, Evelina Maria; Gurning, Sri Handayani (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Coconut flour is obtained from the processing of coconut waste and can be used as a substitute for wheat flour or as additional flour in making bread and cakes. Coconut flour has the advantages of a fairly high protein content, being gluten-free, low digestible carbohydrate content, and higher fiber (cellulose) content compared to other types of flour. Hence, it is very suitable for people who are hypersensitive to gluten or for those who are on a diet. This activity aimed to train the community on processing coconut pulp into coconut flour and its use in making cookies. Utaurano Village in Sangihe Islands Regency is known as one of the centers for making coconut oil. Coconut waste has so far only been thrown away or used as a mixture of animal feed. Community service activities by lecturers and students of the Pharmacy Department of the Manado Ministry of Health Polytechnic include training in processing coconut pulp into coconut flour and its use for making cookies. The implementation of the activity was carried out in several stages, namely preparation, implementation, and evaluation. The results showed that in Utaurano village in Sangihe Islands Regency, coconut waste was produced from the VCO manufacturing process by local UMKM. The waste can be processed into coconut flour and used as a substitute for wheat flour for making cookies. The evaluation results show that counseling and training activities can increase knowledge and skills to utilize coconut waste into products with economic value.